POTENSI MELANOTUS SP. DALAM MENDEGRADASI LIGNIN - SULISTINAH, NUNIK (2008)
Keywords: biodegradation; lignin; oil palm; Melanotus sp

(untitled) (Jurnal Biologi Udayana, 2008)
Ten isolates of fungus were isolated from oil palm stem at oil palm plantation in Medan All of them were tested its abilities to degrade lignin. The results showed that one of them was able to grow on ligninase media and the fungi has the ability to degrade ligin. The fungi is identified as Melanotus sp.